2016
DOI: 10.1111/exd.13144
|View full text |Cite
|
Sign up to set email alerts
|

Acidification of stratum corneum prevents the progression from atopic dermatitis to respiratory allergy

Abstract: The presence of congenitally impaired skin barrier followed by atopic dermatitis (AD) is an initial step in the atopic march. The maintenance of acidic pH in the stratum corneum (SC) has been suggested as a therapeutic or preventive strategy for barrier impairment caused by skin inflammation. To determine whether an AD murine model, flaky tail mice, with inherited filaggrin deficiency could develop airway inflammation by repeated topical application followed by nasal inhalation of house dust mite (HDM) antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 57 publications
(85 reference statements)
0
20
0
3
Order By: Relevance
“…BRP‐39 −/− mice were generated on a C57BL/6 background and maintained as previously described . Flg ft mice, which carry double‐homozygous Flg and matted (ma) gene mutations, with a BALB/c background were kindly provided by Kenji Kabashima (Kyoto University Graduate School of Medicine, Kyoto, Japan), and we backcrossed these with C57BL/6 mice over seven generations. For the OVA‐induced AD model, Flg ft mice were backcrossed with BRP‐39 −/− mice.…”
Section: Methodsmentioning
confidence: 99%
“…BRP‐39 −/− mice were generated on a C57BL/6 background and maintained as previously described . Flg ft mice, which carry double‐homozygous Flg and matted (ma) gene mutations, with a BALB/c background were kindly provided by Kenji Kabashima (Kyoto University Graduate School of Medicine, Kyoto, Japan), and we backcrossed these with C57BL/6 mice over seven generations. For the OVA‐induced AD model, Flg ft mice were backcrossed with BRP‐39 −/− mice.…”
Section: Methodsmentioning
confidence: 99%
“…pH 4) and containing a functioning buffer system were introduced to counteract an increased pH. Treatment with an acidic compared with a neutral cream inhibited the occurrence of atopic dermatitis‐like skin lesions and respiratory allergy in filaggrin‐deficient murine atopic dermatitis models . An emollient with a pH of 4.8 altered skin barrier and microbes in infants at risk for developing atopic dermatitis .…”
Section: Reducing Skin Ph As a Therapeutic Tool In Wound Healing Skimentioning
confidence: 99%
“…Treatment with an acidic compared with a neutral cream inhibited the occurrence of atopic dermatitislike skin lesions and respiratory allergy in filaggrin-deficient murine atopic dermatitis models. [102][103][104] An emollient with a pH of 4.8 altered skin barrier and microbes in infants at risk for developing atopic dermatitis. 105 Skin care products adjusted to pH 4 have been used successfully in acne skin.…”
Section: Reducing Skin Ph As a Therapeutic Tool In Wound Healing Skimentioning
confidence: 99%
“…Importantly, recent studies showed that the epidermal dysfunction-induced elevations in cutaneous cytokines lead to increased levels of proinflammatory cytokines not only in the skin, but also in circulation, supporting not only a pathogenic role for epidermal function in cutaneous and extracutaneous inflammation, but also suggesting a link between cutaneous function and inflammation-associated systemic disorders [17,18]. In addition to epidermal permeability barrier homeostasis, other epidermal functions, such as pH and stratum corneum hydration, also regulate cutaneous functions [19][20][21][22]. Accordingly, improvements in epidermal function could benefit multiple cutaneous and extracutaneous functions [17,[23][24][25].…”
Section: Introductionmentioning
confidence: 97%